Religious Faith of the Chinese - Zhuo, Xinping (China Insights,, 2018)
This book comprehensively examines religious faith in China from the perspective of cultural philosophy and cultural history. It explores the social, political, cultural and spiritual meanings of religions, tracing their historical development and related paradigm shifts. It also analyzes the characteristics of the country's local religions and the process of indigenization of world religions, and describes the peaceful co-existence and harmonious confluence of multiple religions in Chinese spiritual life, revealing the vibrant and diverse colors of its religious culture. Examining these religions' social and cultural functions in contemporary Chinese society, the book demonstrates the rich and complex intertwinement of religious faith, cultural spirit and national disposition among the Chinese people.